Rehabilitation of selective attention and working memory in a child with attention deficit disorder with hyperactivity - Haratti, Malak; Soufi, Naima (Journal of Human Sciences, 2023)
The purpose of this study was knowing speech therapy techniques used in the re education of selective attention (auditory, visual) and working memory (phonological loop, visual space diary) in a child with attention deficit hyperactivity disorder, the descriptive method was applied here, and the sample of the study comprised (08) speech therapists, the tool of the study was online interview about zoom application, the results of the study indicated these techniques are not specific, but it was characterized by flexibility and innovation, and it varied from one specialist to another, this study ended with a number of recommendations and suggestions.